Effect of traction direction and pressure load on the palatal plate on retentive force - Kunihito Yamane; Yuji Sato; Junichi Furuya; Noboru Kitagawa; Naoya Ikemura; Osamu Shimodaira (BMC, 2022)
Abstract Background Recently, a denture adhesive that is easy to clean and contain moisturizing ingredients have been developed for patients with dry mouth. Although the retentive force produced by conventional denture adhesives and oral moisturizers have been compared on models, no study has reported their comparison in the oral cavity. In this study, we aimed to clarify the effects of different directions of traction and loads at the time of pressure contact on the retentive force on a palatal plate made from a dentulous jaw model. Methods A palatal plate was fabricated with thermoplastic resin on a dentulous jaw model, and a loop-shaped traction device was attached to the centre of the palate. The test samples were a cream-type denture adhesive, a denture adhesive for dry mouth, an oral moisturizer, and a denture moisturizer. The specimens were applied to the inner surface of the plate, which was then mounted under vertical pressure. Then, the retentive force was measured, using a digital force gauge, while the plate was pulled in different directions and with different loads. Results No significant difference in retentive force was observed in any of the test samples when the direction of traction was between 45° and 60°. The retentive force of the denture adhesive for dry mouth was significantly higher with a direction of traction of 90° than that of 45° or 60°. The retentive force when oral moisturizer was used was significantly higher in the 90° traction direction than in the 45° direction. There was no significant difference between a force of 4.0 kgf or 5.5 kgf when using a denture adhesive for dry mouth. Comparing the four load size conditions, the larger the load, the higher was the retentive force. Similar results were obtained for the cream-type denture adhesive and denture moisturizer. Significantly higher retentive force was observed for larger loads when oral moisturizer was used. Conclusions The results suggest that the direction of traction and the pressure load affect the retentive force on a palatal plate.